Initial Home Dialysis Is Increased for Rural Patients by Accessing Urban Facilities. Issue 3 (31st March 2022) - Adler, Joel T.; Husain, S. Ali; Xiang, Lingwei; Rodrigue, James R.; Waikar, Sushrut S.
Key Points: Despite having access to fewer facilities that offer home dialysis, rural patients with ESKD are more likely to be on home dialysis. There remains a significant mortality gap between urban and rural patients with ESKD, even when accessing home dialysis. Visual Abstract: Abstract : Background: The 240, 000 rural patients with end stage kidney disease in the United States have less access to nephrology care and higher mortality than those in urban settings. The Advancing American Kidney Health initiative aims to increase the use of home renal replacement therapy. Little is known about how rural patients access home dialysis and the availability and quality of rural dialysis facilities. Methods: Incident dialysis patients in 2017 and their facilities were identified in the United States Renal Data System. Facility quality and service availability were analyzed with descriptive statistics. We assessed the availability of home dialysis methods, depending on rural versus urban counties, and then we used multivariate logistic regression to identify the likelihood of rural patients with home dialysis as their initial modality and the likelihood of rural patients changing to home dialysis within 90 days. Finally, we assessed mortality after dialysis initiation on the basis of patient home location. Results: Of the 97, 930 dialysis initiates, 15, 310 (16%) were rural. Rural dialysis facilities were less likely to offer home dialysis (51% versus 54%, P <0.001). Although a greater proportion of rural patients (9% versus 8%, P <0.001) were on home dialysis, this was achieved by traveling to urban facilities to obtain home dialysis (OR=2.74, P <0.001). After adjusting for patient and facility factors, rural patients had a higher risk of mortality (HR=1.06, P =0.004). Conclusions: Despite having fewer facilities that offer home dialysis, rural patients were more often on home dialysis methods because they traveled to urban facilities, representing an access gap. Even if rural patients accessed home dialysis at urban facilities, rural patients still suffered worse mortality. Future dialysis policy should address this access gap to improve care and overall mortality for rural patients.